P279 MORTALITY RISK DUE TO ACUTE PULMONARY EMBOLISM IN COVID–19 PATIENTS: META–ANALYSIS BASED ON ITALIAN COHORTS. (18th May 2022) - Zuin, M; Rigatelli, G; Bilato, C; Navaro, M; Roncon, L
Abstract: Background: Acute pulmonary embolism (PE) has been recognized as a frequent complication of COVID–19 infection influencing the clinical course and outcomes of these patients. Objectives: We performed a systematic review and meta–analysis to evaluate the mortality risk in COVID–19 Italian patients complicated by acute PE in the short–term period. Methods: The study was performed in accordance with the Preferred Report Items for Systematic Reviews and Meta–analyses (PRISMA) guidelines. PubMed–MEDLINE and Scopus databases were systematically searched for articles, published in English language and enrolling Italian cohorts of COVID–19 patients from inception through October 20, 2021. Mortality risk data were pooled using the Mantel–Haenszel random effects models with odds ratio (OR) as the effect measure with 95% confidence interval (CI). Heterogeneity among studies was assessed using Higgins and Thomson I2 statistic Results: Eight investigations enrolling 1.681 patients (mean age 64.9 years, 1.125 males) met the inclusion criteria and were considered for the analysis. A random–effect model showed that acute PE was presents in 3.1% (95% CI: 1.7 to 5.5%, I2: 80.7%) of COVID–19 Italian patients. Moreover, these subjects were at higher mortality risk compared to those without (OR: 1.76, 95% CI: 1.26–2.47, p = 0.001, I2=0%) (Figure 1 ), Sensitivity analysis confirmed yielded results. Conclusions: In Italian COVID–19 patients, acute PE was present in one patient out of four and significantly associated with a higher mortality risk in the short–term period. The identification of acute PE in these patients remains critical to promptly identify vulnerable populations who would require prioritization in treatment and prevention and close monitoring.